Predictors of insufficient peak amikacin concentration in critically ill patients on extracorporeal membrane oxygenation - Cyril Touchard; Alexandra Aubry; Philippine Eloy; Nicolas Bréchot; Guillaume Lebreton; Guillaume Franchineau; Sebastien Besset; Guillaume Hékimian; Ania Nieszkowska; Pascal Leprince; Charles-Edouard Luyt; Alain Combes; et al. (Critical Care, 2018)
Abstract Background Amikacin infusion requires targeting a peak serum concentration (Cmax) 8–10 times the minimal inhibitory concentration, corresponding to a Cmax of 60–80 mg/L for the least susceptible bacteria to theoretically prevent therapeutic failure. Because drug pharmacokinetics on extracorporeal membrane oxygenation (ECMO) are challenging, we undertook this study to assess the frequency of insufficient amikacin Cmax in critically ill patients on ECMO and to identify relative risk factors. Methods This was a prospective, observational, monocentric study in a university hospital. Patients on ECMO who received an amikacin loading dose for suspected Gram-negative infections were included. The amikacin loading dose of 25 mg/kg total body weight was administered intravenously and Cmax was measured 30 min after the end of the infusion. Independent predicators of Cmax < 60 mg/L after the first amikacin infusion were identified with mixed-model multivariable analyses. Various dosing simulations were performed to assess the probability of reaching 60 mg/L < Cmax < 80 mg/L. Results A total of 106 patients on venoarterial ECMO (VA-ECMO) (68%) or venovenous-ECMO (32%) were included. At inclusion, their median (1st; 3rd quartile) Sequential Organ-Failure Assessment score was 15 (12; 18) and 54 patients (51%) were on renal replacement therapy. Overall ICU mortality was 54%. Cmax was < 60 mg/L in 41 patients (39%). Independent risk factors for amikacin under-dosing were body mass index (BMI) < 22 kg/m2 and a positive 24-h fluid balance. Using dosing simulation, increasing the amikacin dosing regimen to 30 mg/kg and 35 mg/kg of body weight when the 24-h fluid balance is positive and the BMI is ≥ 22 kg/m2 or < 22 kg/m2 (Table 3), respectively, would have potentially led to the therapeutic target being reached in 42% of patients while reducing under-dosing to 23% of patients. Conclusions ECMO-treated patients were under-dosed for amikacin in one third of cases. Increasing the dose to 35 mg/kg of body weight in low-BMI patients and those with positive 24-h fluid balance on ECMO to reach adequate targeted concentrations should be investigated.